Description Context of Factors that Influence Pregnant Women in the Third Trimester - Yohana Bangngu; Alfonsa I. L. Seran; Mariance E. Lepa (Journal of Tropical Diseases and Health Science, 2026)
The research promlem in the research of this kind is how is the description context of factors that influence pregnant women in the third trimester in the Local Government Clinic of Sikumana? Thus, the aim of this research is to know the description context of factors that influence pregnant women in the third trimester in the Local Government Clinic of Sikumana. The research method used in this research is qualitative-descriptive method. The population in this research were all pregnant women with anemia during three mounths (2016-2018) in the Local Government Clinic of Sikumana with the amount of 712 people and 35 people were used as the sample of this study. The collection data was done by the distribution of questionnaire sheets. While the analysis data was done by the Chi-Square Test. The result of this research shows that there is significant relationship between age, length of pregnance, ANC frequency, nutrient status, education and degree of iron tablet consumption at the significance level ≤0,05.